WI-1, a novel 120-kilodalton surface protein on Blastomyces dermatitidis yeast cells, is a target antigen of cell-mediated immunity in human blastomycosis. - Klein, B S (1992)
A large body of experimental data has demonstrated the central role of T cells in acquired resistance to the dimorphic fungus Blastomyces dermatitidis. We examined the human T-cell response to WI-1, a 120-kDa B. dermatitidis yeast cell surface protein recently shown to be an immunodominant antigen of the B-cell response in infected humans. Peripheral blood lymphocytes from 10 blastomycosis patients studied proliferated in response to WI-1 (mean, 19,431 cpm) and to the standard, crude cell wall antigen, Blastomyces alkali- and water-soluble antigen (B-ASWS) (mean, 19,131 cpm); lymphocytes from 10 histoplasmosis patients and 10 normal control subjects did not respond to WI-1. WI-1 stimulation of patient lymphocytes and rechallenge with WI-1 or B-ASWS showed that the antigens share immunodominant epitopes. Of 100 WI-1-responsive T-cell clones derived from peripheral blood, 10 were studied in detail to assess the phenotype, function, and ligands recognized. The clones exhibit the CD3+ CD4+ phenotype of helper T cells; 2 of 10 clones (and 21% of antigen-stimulated peripheral blood lymphocytes) use the V beta 8 T-cell receptor gene element to respond to WI-1. All the clones proliferate in response to both WI-1 and B-ASWS but not other fungal antigens, and some mediate potent cytolytic effects on WI-1- and B-ASWS-labeled targets. WI-1 recognition requires antigen processing and presentation of epitopes in association with HLA-DR (to noncytolytic clones) and HLA-DP (to cytolytic clones). From these findings, we conclude that CD4+ T cells with regulatory and cytolytic properties are involved in the development of acquired resistance of B. dermatitidis, that the cells are directed against WI-1, and that the manner of display of WI-1 peptide epitopes in conjunction with major histocompatibility complex class II may influence the profile of the immune response.